Design and evaluation of a robust carbon-fiber composite beam collimator to protect the machine from accidental injection kicker firing events in the SuperKEKB positron ring - S. Terui; M. Kikuchi; A. Natochii; K. Watanabe; T. Mimashi; T. Ishibashi; M. Shirai; K. Shibata; Y. Suetsugu; K. Iijima; M. Yao; T. Kurihara (Physical Review Accelerators and Beams)
The collimators in the SuperKEKB rings are indispensable for reducing beam background noise in the Belle II particle detectors and protecting essential components, such as the final focusing superconducting quadrupole magnets, from beams that may deviate into abnormal orbits. This study developed a new robust collimator using a carbon-fiber composite (CFC) as the head material to receive a beam kicked by the accidental firing of the injection kicker. Simulation results confirmed that the new CFC collimator suppressed the temperature rise in the collimator head caused by a beam hit through accidental firing of an injection kicker more effectively than the conventional tungsten collimator. Additionally, radiation damage to the particle detector was reduced to a sufficiently low level with the new CFC collimator. When CFC was adopted as the head material, the head length was longer, and thus the impedance was higher than that of tungsten. Calculations confirmed that using CFC as the head material of the D06H3 horizontal collimator did not result in beam instability for a head length of up to 160 mm. Further, these calculations also verified that the temperature of the surface of collimator jaws irradiated by synchrotron radiation remained within 100 °C, despite the steeper taper angle owing to the 160 mm head length. Initial copper and CFC bonding tests revealed cracks in the CFC caused by stress owing to the difference in thermal expansion. In subsequent bonding tests, slits were made in the copper to alleviate this stress and prevent the formation of cracks in the CFC. A sample with copper slits exhibited no cracks in the CFC. Based on these measurements and calculations, we manufactured a collimator using CFC as the head material and installed it within the SuperKEKB LER ring as a countermeasure against accidental kicker fires. The installed collimators were also evaluated for issues resulting from factors such as beam impedance, the ability to protect the Belle II particle detectors during accidental fires, and the ability to cool the high-intensity synchrotron radiation surface. All evaluated items indicated no major issues.